Lumbosacral osteosarcoma with dural spread, skip lesions and intravascular extension: A case report - Karim, Noor Khairiah A.; Naser, Mohamad Nazrulhisham Mad; George, John (Malaysian Medical Association, 2018)
Primary osteosarcoma of the spine is indeed rare and only several sporadic cases have been reported. It tends to occur in a slightly older age group than those with appendicular skeleton tumours. We present here an unusual case of aggressive lumbosacral osteosarcoma in a young teenager complicated by extensive dural spread, skip lesions and intravascular extension. Although a histopathological examination is mandatory to establish the diagnosis, this case emphasises the need of imaging to ascertain the full extent of disease spread especially in deciding the type of treatment to be instituted and to evaluate the response to the treatment.